Perkembangan Sosial Anak Usia Dini Melalui Teman Sebaya di TK Al Fiqri School - Fauziah Nasution; Nur Hijriyati Waisa; Salsabila Aulia; Iis Rosidah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
It is important to prioritize learning through playing with peers because social development plays a very important role in the development that occurs in children. Nowadays, many students face situations where they are unable to interact with their peers. Therefore, this study aims to examine the social development of underage children through interactions with equal peers. This research used a qualitative descriptive approach and involved all students in class 3A of the AL FIQRI SCHOOL Kindergarten, as well as teachers and the school principal. Information about children's social development is collected through interviews, observation and documentation. Qualitative analysis was used in this research. From the results of research conducted, it is proven that interaction with peers plays a very important role in children's social development. Through this interaction, children can learn to obey rules, provide help to friends in situations such as studying, and share with their friends. Therefore, it can be concluded that peers have a significant influence on the social development of early childhood. The aim of this research is to evaluate the development of children's social relationships with peers.